Innovative Carrot Flour in Making Pasta and Bread.: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The research aimed to prove the two constable variables' concerns: first, if the alternative material used is suited for substituting the raw material, which intrinsic views of the study, and second, if the product done would trend and be recognised by the respondents during experimentation. However, the study shows the possible perception of alternative products as they might be used for certain instances of scarcity. To view it holistically, the researchers built and established an idea for carrots to become substitutes for wheat flour for making bread and pasta.   The product seems unfamiliar to the respondent during and after the experimentation, although it’s introduced as a prototype and subject to the study. The product has received varied feedback during experimentation.                                                                             All of their response is part of data collection on sampling, which is the survey method. To sum up, the study has aimed its goal based on the respondent's response that carrot flour would be an alternative to wheat flour for making pasta and bread. The study used online survey sampling, in which the researcher collects all the data; thus, the products were exposed before the sampling was held. Online survey sampling is convenient when it comes to time and hassle-free data collection for the respondents, further used by the researcher to collect and interpret the data as easily as feasible.  The study is to acquire more data to prove that the product is visibly viewed as a substitute for the alternative in future use. In addition, this study proves the hypothesis about the product is not null like data interpretations and based upon the respondent’s response.
Keywords: Innovative Carrot Flour